Analysis of the articular cartilage T1ρ and T2 relaxation times changes after ACL reconstruction in injured and contralateral knees and relationships with bone shape. Issue 3 (19th September 2016) - Pedoia, Valentina; Su, Favian; Amano, Keiko; Li, Qi; McCulloch, Charles E.; Souza, Richard B.; Link, Thomas M.; Ma, Benjamin C.; Li, Xiaojuan
ABSTRACT: The objectives of this study were twofold: (1) to evaluate the longitudinal change in cartilage T1ρ and T2 6‐ and 12‐months after ACL reconstruction (ACLR) in both reconstructed and intact contralateral knees with the aim of validating the role of the contralateral knee as an internal control in longitudinal studies; (2) to explore relationships between bone shape at the time of injury and the progression of T1ρ and T2 over 12‐months after ACLR. T1ρ and T2 cartilage relaxation times and 3D MRI‐based statistical shape modeling (SSM) of tibia and femur were computed for both knees of forty ACL‐injured patients and 15 healthy controls. ACL subjects were scanned 8.4 ± 6.4 weeks after injury (2.4 ± 3.7 weeks prior to ACLR), 6‐ and 12‐months after ACLR. Longitudinal changes in T1ρ and T2 values were assessed using linear mixed model, and partial correlation coefficients were calculated between bone shape and longitudinal changes in T1ρ and T2 values. Significant longitudinal increases in T1ρ and T2 values were observed in reconstructed and contralateral knees 6‐months after ACLR. Tibial bone shape features, associated with the medial plateau height and width, were observed to be correlated with cartilage T1ρ and T2 progression in reconstructed knees. Our results suggest that caution should be used in considering contralateral knee as internal controls in longitudinal ACL studies and 3D MRI‐based‐SSM might serve as an imaging biomarker for the early stratification of patients at risk for developing post‐traumatic accelerated cartilage degeneration and potentially osteoarthritis after ACL tear. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:707–717, 2017.